Desapropriar para assentar: um direito e reforma agrária no Rio Grande do Sul (1960-2009) - Silva, Caroline da (2019)
The agrarian question of South-Rio-Grandense involving the expropriation of lands by social interest is a new and necessary subject in the academic environment. Since, from the study of sources of the National Institute of Colonization and Agrarian Reform (INCRA), we can enter a world of litigation involving land tenure. In the study in question are 133 rural properties that for some reason failed to fulfill the social function. Properties located in 15 regions of the state differentially territorialized by their agents, who brought different techniques and modes of production. As much as the territory was receiving these subjects, others were excluded from the new dynamics of production and formation of latifundia. Where were they going? How did they survive? Who helped them? It is from the restlessness in the countryside that arises not only simple laws but also social movements that act against this property of restricted land there are some. In this sense, this research, which studied INCRA's administrative processes and judicial processes, seeks not only to map the number of expropriations in the period from 1960 to 2009, but also to map the distribution of these expropriations in the state, and in which region or region there were the largest number of expropriations. Also, it is necessary to understand to what extent an agrarian reform was made in that period, whether it was according to the demands of rural social movements or whether it was the way the state thought it would be best. However, the path that land expropriation takes is sometimes long. From the denunciation of the unproductive landlord, the inspection of the property, the decree of expropriation to put an end to creating the settlement requires a new struggle. From the creation of 133 rural settlements that received a certain number of families from the size of the property area, it is possible to visualize that many settlements created in areas that were not suitable for the settlement (these information, present in the own reports of the INCRA survey)